Breakdown resistance analysis of traction motor winding insulation under thermal ageing - Gyftakis, K. N.; Panagiotou, P. A.; Lophitis, Neophytos; Howey, D. A.; McCulloch, M. D. (My University, 2017)
Stator inter-Turn faults are among the most important electric motor failures as they progress fast and lead to catastrophic motor breakdowns. Inter-Turn faults are caused due to the windings' insulation degradation. The main stress which deteriorates the insulation is the thermal one. Proper understanding of how this stress influences the electrical properties of insulation over time may lead to reliable prognosis and estimation of the motor's remaining useful life. In transport applications where reliability and safety come first it is a critical issue. In this paper, extensive experimental testing and statistical analysis of thin film insulation for traction motor windings has been performed under fixed thermal stress. The results indicate that for high thermal stress the electrical properties of the insulation material present a non-monotonic behavior thus proving the well-known and established Arrhenius law inadequate for modelling this type of problems and estimating the remaining useful life of thin film insulation materials.
Keywords: Breakdown Voltage; Degradation; Electric Motor; Insulation; Prognosis